2022
DOI: 10.1088/1755-1315/977/1/012025
|View full text |Cite
|
Sign up to set email alerts
|

The effect of manure and ascorbic acid to the growth of Vetiveria zizanioides L. in saline soil

Abstract: Vetiveria zizanioides was known as vetiver that produces a good quality oil and is also competent in foreign markets. This study aims to determine the effect of manure and ascorbic acid on the growth of vetiver on saline soil by applying the appropriate dose of manure and ascorbic acid for optimal growth. The methodology was done using a randomized block design with three replicates and consisted of 2 factors, i.e., manure level (K) and the ascorbic acid concentration (A). The results suggested an interaction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 20 publications
3
3
0
Order By: Relevance
“…The abovementioned results were confirmed during the two successive seasons. Similar favorable effects on plant growth due to the organic applications of (AsA) were noticed by Nassar et al (2019) on basil plant, Azizi et al (2021) on Calendula officinalis L., Hassan et al (2021) on Hordeum vulgare L., and Novita et al (2022) on Vetiveria zizanioides L. However, the results for CAA are as stated with those reported by Junxi et al (2010) on Chinese cabbage, Mohammadipour and Souri (2019) on Coriandrum sativum L., and Ahmed et al (2020) on borage plant. However, these results for Com are in harmony with those reported by Abo-Kora and Mohsen (2016) on basil plant, and Golijan and Marković (2018) on fennel plant.…”
Section: Vegetative Growth Characteristicssupporting
confidence: 74%
See 1 more Smart Citation
“…The abovementioned results were confirmed during the two successive seasons. Similar favorable effects on plant growth due to the organic applications of (AsA) were noticed by Nassar et al (2019) on basil plant, Azizi et al (2021) on Calendula officinalis L., Hassan et al (2021) on Hordeum vulgare L., and Novita et al (2022) on Vetiveria zizanioides L. However, the results for CAA are as stated with those reported by Junxi et al (2010) on Chinese cabbage, Mohammadipour and Souri (2019) on Coriandrum sativum L., and Ahmed et al (2020) on borage plant. However, these results for Com are in harmony with those reported by Abo-Kora and Mohsen (2016) on basil plant, and Golijan and Marković (2018) on fennel plant.…”
Section: Vegetative Growth Characteristicssupporting
confidence: 74%
“…Such results were confirmed during the two tested seasons. Similar enhancement effects on chemical analysis due to applying organic applications were reported by Mohammadipour and Souri (2019) on Coriandrum sativum L. Azizi et al (2021) on Calendula officinalis L. and Novita et al (2022) on Vetiveria zizanioides L.…”
Section: Chemical Analysissupporting
confidence: 73%
“…The vetiver grass was able to thrive in swine wastewater, according to Ngilangil et al, as shown by the height of its shoots and the length of its roots, which were 65.50 and 65.80 cm after 9 weeks of culture (Ngilangil & Quinquito, 2020). According to Novita et al., ascorbic acid and manure had best effects on vetiver grass growth in salty soil, with plant heights of 145.71 and 145.61 cm, respectively (Novita et al., 2022).…”
Section: Resultsmentioning
confidence: 99%
“…Nutrient solution concentration (mg/L) The vetiver plant, Vetiveria zizanioides L., is a species of the Graminae family (Novita et al, 2022). Since vetiver has difficulty producing seeds germinate, the usual method of proliferation is through root division.…”
Section: S Nomentioning
confidence: 99%
See 1 more Smart Citation